Digitized Evaluation of Academic Opportunities to Learn (OTLs) Concerning Linguistically Responsive Teaching (LRT): Descriptive Results from Nine Universities - Svenja Lemmrich; Sina Spiekermeier Gimenes; Timo Ehmke (MDPI AG, 2024)
Teachers in Germany are not adequately prepared to teach in a linguistically responsive way. To change that, multiple development and research projects in this area have been established over the past decade. Recent studies show that pre-service teachers still have few opportunities to learn (OTLs) in the field of linguistically responsive teaching (LRT). This study aimed to transfer the theoretical model and the DaZKom test into pre-service teacher training and evaluate LRT-relevant OTLs at nine different universities across Germany with 1649 pre-service teachers. We focused on how LRT-relevant OTLs were perceived by pre-service teachers, how LRT-related OTLs and pre-service teachers' academic backgrounds (course of studies and experience) were related, and how OTLs impacted LRT competence. This study was conducted during the COVID-19 pandemic. Therefore, the teacher training and evaluations were conducted digitally. We found that pre-service teachers report a relatively low number of LRT-relevant OTLs in their studies. In particular, LRT-relevant activities have so far been taught very rarely at universities. Also, different emphases still prevail at universities regarding the qualitative and quantitative offer of LRT-relevant OTLs, because of differences among the nine participating universities. Based on these findings, we recommend that universities offer LRT-relevant learning opportunities in the curriculum.